2006
DOI: 10.1176/appi.ajp.163.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Risk During Antidepressant Treatment

Abstract: The risk of suicide during acute-phase antidepressant treatment is approximately one in 3,000 treatment episodes, and risk of serious suicide attempt is approximately one in 1,000. Available data do not indicate a significant increase in risk of suicide or serious suicide attempt after starting treatment with newer antidepressant drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
208
1
12

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 359 publications
(236 citation statements)
references
References 24 publications
15
208
1
12
Order By: Relevance
“…48,49 Still other studies have used large databases to carry out naturalistic studies of possible associations between antidepressant use and suicidality. [50][51][52][53] In the only 1 of these studies that focused exclusively on youth, Valuck et al 50 conducted a propensity-adjusted retrospective cohort study to examine links between antidepressant treatment and suicide attempts in depressed adolescents (aged 12-18) by using a community sample of managed care enrollees. They found no increase in suicide rates with treatment with SSRIs, other antidepressants, or multiple antidepressants after a diagnosis of MDD, finding instead that treatment for at least 6 months reduced the likelihood of suicide attempts compared with treatment for less than 8 weeks.…”
Section: Antidepressant Treatmentmentioning
confidence: 99%
“…48,49 Still other studies have used large databases to carry out naturalistic studies of possible associations between antidepressant use and suicidality. [50][51][52][53] In the only 1 of these studies that focused exclusively on youth, Valuck et al 50 conducted a propensity-adjusted retrospective cohort study to examine links between antidepressant treatment and suicide attempts in depressed adolescents (aged 12-18) by using a community sample of managed care enrollees. They found no increase in suicide rates with treatment with SSRIs, other antidepressants, or multiple antidepressants after a diagnosis of MDD, finding instead that treatment for at least 6 months reduced the likelihood of suicide attempts compared with treatment for less than 8 weeks.…”
Section: Antidepressant Treatmentmentioning
confidence: 99%
“…While the estimated risk remained relatively stable over the next six months, their confidence intervals were wide, validating the lack to the number of observed events. Researchers assert that a significant increase of suicide risks or serious suicidal attempts existed after initiating SSRI therapy 48 . These findings were confirmed by Simon & Savarino, thus proving the reduction in the suicide rate after AD treatment 49 .…”
Section: Elapsed Time In Antidepressant Treatmentmentioning
confidence: 99%
“…22 However, in close parallel with the FDA review of data from randomized trials of modern antidepressants, 2,11 a recent review of clinical cohort studies 23 found evidence of age-related increases (adolescents) and decreases (older adults) of suicidal risks that included attempts and fatalities (see Figure 1). Dr. Fawcett: Simon et al 24 reported data showing that suicide attempt risk was highest during the month prior to antidepressant prescription and decreased throughout treatment (Figure 2). Dr. Baldessarini: Most large case series or cohort studies look favorable, but, in the randomized controlled literature, little evidence clarifies whether antidepressants specifically worsen or help suicidal behaviors (as opposed to self-reported suicidal ideation).…”
Section: Dr Fawcettmentioning
confidence: 99%
“…The suicide intervention information significantly reduced suicide attempts among students (P < .05). 24 Bars indicate 95% confidence intervals. (Table 2).…”
Section: -3mentioning
confidence: 99%